Development Perspectives from Creative Entrepreneurship in Alagoas / Perspectivas de Desenvolvimento a partir do Empreendedorismo Criativo em Alagoas - Orlando Ramos do Nascimento Júnior; Katia Jeane Alves Mota; Luiz Geraldo Rodrigues de Gusmão; Erich Gustavo Santos Ramos (Universidade Estadual de Alagoas, 2018)
The objective of this study is to present some considerations on the so-called creative economy and it's development in the State of Alagoas, in the face of the State's economic development prospects. Through a brief approach on the origin and design of creative economy and economic heritage of the State, it was possible to draw a parallel between the evolution of the conception of culture and creativity for the promotion of development, since the concept of cultural Industry to your application in the socioeconomic scenario of Alagoas. Through bibliographical and exploratory research, in which some authors were used such as Adorno and Horkheimer, with The Critical Theory about "mass culture" and economy and Howkins, Florida, about the current design of the relationship between creativity, culture and economy; Carvalho, on the nearby state economy and Verdi and Pires, on micro and small enterprises; National mappings, which enabled the understanding of the socioeconomic reality of the State.